1977
DOI: 10.1107/s0567740877011169
|View full text |Cite
|
Sign up to set email alerts
|

Crystal and molecular structure of glycyrrhetinic acid acetone monohydrate

Abstract: KATSUO KATO, ISAO KAWADA UND TATSUO TAKAHASHI 3443 den unter Annahme dieses Atomformfaktors verfeinerten Angleichungsfaktoren ffir die Reflexgruppen mit k -0(mod 3) und k ---0(rood 5) steht mit dem experimentell ermittelten Weft im Einklang. Die aus dem obengenannten 'Zellinhalt' errechnete Dichte betriigt 4,53 g cm -3 und stimmt mit dem von Takahashi et al. (1971) Glycyrrhetinic acid acetone monohydrate (1 : 1 : 1) crystallizes in the orthorhombic space group P21212 with a = 11.541, b = 36.328, c = 7-406 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 1 publication
(1 reference statement)
2
15
0
Order By: Relevance
“…This also revealed that the stereochemistry12 of the starting material 8 had been retained in the product without any epimerization of the CD rings taking place under the basic conditions of the reactions.…”
Section: Resultsmentioning
confidence: 83%
“…This also revealed that the stereochemistry12 of the starting material 8 had been retained in the product without any epimerization of the CD rings taking place under the basic conditions of the reactions.…”
Section: Resultsmentioning
confidence: 83%
“…1. The GA fragment (C1 through C30, O1, O4, O5) features usual bond lengths, bond angles, and conformation (Campsteyn et al, 1977;Alvarez-Larena et al, 2007;Beseda et al, 2010;Czollner et al, 2011). There are four six-membered saturated carbocycles (A, B, D, and E) in chair and the unsaturated ring C in half-chair conformation (Fig.…”
Section: Data Collectionmentioning
confidence: 98%
“…For the synthesis of new derivatives of 18-glycyrrhetinic acid and their effect on 11-hydroxysteroid dehydrogenase, see: Su et al (2004); Beseda et al (2010); Amer et al (2010). For the crystal structure of 18-glycyrrhetinic acid, see: Campsteyn et al (1977); Alvarez-Larena et al (2007). For the crystal structures of derivatives of 18-glycyrrhetinic acid, see: ; Amer et al (2010); Czollner et al (2011).…”
Section: Related Literaturementioning
confidence: 99%
“…For glycyrrhetinic acid (GE), with the OH group instead of the succinyl group at C3, three solvated crystal structures have been reported (Beseda et al, 2010;Campsteyn et al, 1977;Alvarez-Larena et al, 2007) and two of them exhibit a type of aggregation similar to that in CBXH 2 . In the dimethylsulfoxide solvate (Beseda et al, 2010) the unit-cell parameters b (6.5 Å , along the ribbon) and a (13.1 Å ) correspond to theandmode arrangement of ribbons within the layer as found in (2).…”
Section: Tablementioning
confidence: 99%
“…These three pharmaceutically relevant agents seem to be perfect candidates to investigate the impact of changes in hydrophilicity and the size of headgroups on the supramolecular organization of molecules in the solid state. For GE three solvated crystal structures are known (Alvarez-Larena et al, 2007;Beseda et al, 2010;Campsteyn et al, 1977). The self-asssembly mode of GA in its neutral and ionized forms has been recently reported (Tykarska et al, 2012;Tykarska & Gdaniec, 2013;Tykarska et al, 2014) but the crystal structure of CBXH 2 has not been studied by diffraction techniques until now.…”
Section: Introductionmentioning
confidence: 99%